The Prognostic Value of Percentage of Positive Biopsy Cores, Percentage of Cancer Volume, and Maximum Involvement of Biopsy Cores in Prostate Cancer Patients Receiving Proton and Photon Beam Therapy. (June 2014) - Slater, Jason M.; Bush, David A.; Grove, Roger; Slater, Jerry D.
The purpose of the study is to compare the prognostic value of percentage of positive biopsy cores (PPBC), percentage of cancer volume (PCV), and maximum involvement of biopsy cores (MIBC) as a prognostic factor in low- and intermediate-risk patients with clinically localized prostate cancer who received proton or photon beam therapy. Four hundred and fifty-nine patients with clinically localized prostate carcinoma who were treated with proton or photon beam therapy at Loma Linda University Medical Center were used for this analysis. Patients were treated with a median dose of 74.0 Gy (range 70.2–79.2) proton or combined proton/photon beam radiotherapy. Pathology reports were reviewed and PPBC, PCV, and MIBC were recorded. Analysis of biochemical no evidence of disease (bNED) outcome was assessed using Kaplan-Meier analyses. Cox regression multivariate analyses were performed to assess the impact of the biopsy factors on survival. Results: 285, 291, and 291 patients had biopsy information available for analysis, respectively. Survival analysis showed that a higher PPBC, PCV, and MIBC were each individually associated with an increased risk of biochemical failure on univariate analysis ( p < 0.01). Only PPBC and PCV were associated with an increased risk of biochemical failure on multivariate analysis, adjusting for age, NCCN risk group, and dose ( p < 0.01). When isolating the intermediate-risk group, only PPBC and PCV were statistically significant on multivariate analysis. Multivariate analysis of the intermediate-risk group comparing PPBC and PCV showed that PPBC was not a significant predictor of biochemical failure, while PCV was a significant predictor of biochemical failure ( p = 0.37 and p = 0.03, respectively). Conclusion: PPBC and PCV can potentially be used for additional risk stratification of intermediate-risk patients with PCV potentially being the most clinically relevant predictor bNED survival. MIBC was not found to have utility in the prognosis of low- and intermediate-risk patients.